2013
DOI: 10.21273/hortsci.48.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Effects of Three Types of White Light-emitting Diodes on Plant Growth and Development: Absolute versus Relative Amounts of Blue Light

Abstract: Light-emitting diodes (LEDs) are a rapidly developing technology for plant growth lighting and have become a powerful tool for understanding the spectral effects of light on plants. Several studies have shown that some blue light is necessary for normal growth and development, but the effects of blue light appear to be species-dependent and may interact with other wavelengths of light as well as photosynthetic photon flux (PPF). We report the photobiological effects of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 20 publications
10
91
1
1
Order By: Relevance
“…Wheat is one of the core grain crops in BLSS. Previous study has shown that although wheat is not sensitive to the blue light dose induction (Dougher and Bugbee , Cope and Bugbee ), the combination of red–blue LED spectra can improve its output and photosynthetic rate (Goins et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is one of the core grain crops in BLSS. Previous study has shown that although wheat is not sensitive to the blue light dose induction (Dougher and Bugbee , Cope and Bugbee ), the combination of red–blue LED spectra can improve its output and photosynthetic rate (Goins et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to major pigments such as chlorophylls, phycobilins and carotenoids, there are a wide range of photoreceptors which react to the quality of the light, affecting the development of the microalgae [8]. For plants, a vast amount of research has been performed in this area and it is well-known that light quality plays a major signalling role in plant development [1,3,6,17]. However, less is known about the effects of light quality on photosynthetic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Current research demonstrates that light quality can impact plant growth and biomass accumulation of specialty crops in controlled environments . In a recent study, shoot FM (g per plant) in 28‐day‐old Chinese cabbage ( Brassica chinensis ) was significantly higher under high pressure sodium (HPS) lighting compared to a 7: 1 ratio of red (650 nm) and blue (470 nm) LED light at an equal intensity of 391 ± 24 µmol m −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%